STRATEGI PEMIMPIN DALAM MENGATASI KONFLIK DALAM TIM - Hans Filbert Nadeak; Grace Yosepha Sinaga; Jemima Fevriera Bangun; Salsabila; Nurhasanah Siregar (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This study aims to analyze the strategies used by leaders in resolving conflicts that occur within a team. Conflict is an inevitable aspect of any organization but can yield positive outcomes when managed effectively. This research employs a qualitative method through direct and indirect interviews with two respondents: a large kiosk owner on MMTC Street and a night market owner on Makmur Street, Medan Tembung. The findings indicate that effective leadership strategies in handling conflicts include the leader’s ability to act as a “conflict detective” by analyzing root causes, serving as a neutral dialogue facilitator, and promoting collaborative solutions that benefit all parties involved. In addition, leaders need to implement preventive measures through clear organizational structures and open communication to maintain team harmony. Therefore, a leader’s success in managing conflict is not only measured by their ability to resolve issues but also by their capacity to build an adaptive, empathetic, and collaborative work culture.